Pengaruh Debt to Equity Ratio dan Current Ratio terhadap Return on Asset pada Perusahaan Rokok di Bursa Efek Indonesia Tahun 2015–2024 - Chairunnisa, Siti; Lestari, Dheri Febiyani; Rahayu, Isyana (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of Debt to Equity Ratio (DER) and Current Ratio (CR) on Return on Assets (ROA) in cigarette companies listed on the Indonesia Stock Exchange (IDX) during the period 2015–2024. The research method applied is quantitative analysis with a multiple linear regression approach. Data were collected from annual financial statements of the sampled companies. The findings indicate that both DER and CR have no significant effect on ROA. This suggests that leverage and liquidity levels are not the primary determinants of a company’s ability to generate profits from its assets. Furthermore, the F-test in this research is applied as a model suitability test rather than a simultaneous significance test. Therefore, it can be concluded that variations in ROA of cigarette companies are influenced by other factors beyond DER and CR. The results of this study are expected to provide useful insights for investors, management, and future researchers in understanding the financial performance of the cigarette industry sector in Indonesia.